2018
DOI: 10.3329/kyamcj.v8i2.35696
|View full text |Cite
|
Sign up to set email alerts
|

Study on outcome of ischemic stroke patient with atrial fibrillation

Abstract: Background: Atrial fibrillation (AF) is a common arrhythmia and a major risk factor for ischemic stroke, especially in the elderly patients. Patients with non-valvular AF have a 5-fold excess risk of stroke recurrence and case-fatality rate.Objectives: This study was to evaluate the prevalence of AF and its influence on prognosis in patients with ischemic stroke.Materials & Methods: Total 125 patients with ischaemic stroke were enrolled in this study. Initially they were divided into two groups by ECG - th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
2
1
1
Order By: Relevance
“…A Multicenter Multinational Hospital–A-based study in Europe has also reported 57.9% females. 34 However, in contrast to our finding, Mallick et al 31 reported male predominance. Furthermore, the current study revealed that patients with AF were older at the time of stroke onset, with a mean age at stroke onset of (65.75 years ±16.4 years vs 63 years ±13.58 years).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…A Multicenter Multinational Hospital–A-based study in Europe has also reported 57.9% females. 34 However, in contrast to our finding, Mallick et al 31 reported male predominance. Furthermore, the current study revealed that patients with AF were older at the time of stroke onset, with a mean age at stroke onset of (65.75 years ±16.4 years vs 63 years ±13.58 years).…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, the current study revealed that patients with AF were older at the time of stroke onset, with a mean age at stroke onset of (65.75 years ±16.4 years vs 63 years ±13.58 years). The findings were consistent with those of previous studies conducted in Cameroon, 17 and Bangladesh, 31 but the Multicenter Multinational Hospital-Based Registry in the European community 34 revealed a somewhat higher mean age at a stroke on set (77.3 years ±9.6 years vs 70.6 years ±12.9 years). The disparity could be explained by differences in sample size, research area, and age disparities in the studied population.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study found that, disability was shown to be significantly higher for 45 patients with AF than the non-AF group (84.44% vs 24.16%). Similarly, in previous study ischemic stroke patients following an atrial fibrillation disease had increased disability [14,17]. AF was clearly associated with an increased risk of severe neurological deficits.…”
Section: Discussionsupporting
confidence: 57%